Two coupled mutations abolished the binding of CEBPB to the promoter of CXCL14 that displayed an antiviral effect on PRRSV by activating IFN signaling. Issue 8 (10th July 2020) - Niu, Lizhu; Zheng, Zhiwei; Xue, Qianjing; Cheng, Huijun; Liu, Ying; Wang, Huanling; Hu, Xueying; Zhang, Anding; Liu, Bang; Xu, Xuewen
Abstract: Porcine reproductive and respiratory syndrome (PRRS) is the most economically important infectious disease of pigs worldwide. Our previous study revealed that Tongcheng (TC) pigs display higher resistance to PRRS than Largewhite (LW) pigs, but the genetic mechanism remains unknown. Here, we first confirmed that CXCL14 was downregulated in lungs and porcine alveolar macrophages (PAMs) responding to PRRS virus (PRRSV) infection, but the decline in LW pigs was more obvious than that in TC pigs. Then, we found that the overexpression of CXCL14 activated type‐I interferon (IFN‐I) signaling by upregulating interferon beta (IFNB), which plays a major role in the antiviral effect. To further decipher the mechanism underlying its differential expression, we characterized the core promoter of CXCL14 as being located from −145 to 276 bp of the transcription start site (TSS) and identified two main haplotypes that displayed significant differential transcriptional activities. We further identified two coupled point mutations that altered the binding status of CEBPB and were responsible for the differential expression in TC and LW pigs. The regulatory effect of CEBPB on CXCL14 was further confirmed by RNA interference (RNAi) and chromatin immunoprecipitation (ChIP), providing crucial clues for deciphering the mechanism of CXCL14 downregulation in unusual conditions. The present study revealed the potential antiviral effect of CXCL14, occurring via activation of interferon signaling, and suggested that CXCL14 contributes to the PRRS resistance of TC pigs.